The investigation of radiation effect on tungsten and molybdenum materials (International Journal of Mathematics and Physics, 2024)
This work studied damage and erosion of the tungsten and molybdenum after exposure to deuterium ions of a Plasma focus device.  The main purpose and idea of this research work was an experimental investigation of surface changes on the tungsten and molybdenum materials at deuterium optimal gas pressure in the chamber of a PF device.  Before and after irradiation the sample surfaces were analyzed using SEM, AFM and an optical microscope. The analysis showed that the change in surface relieves, different types of damage on materials dependent on irradiation parameters. With increasing the number of shots the micro-cracks, and radiation swelling for molybdenum, also the crater, bubbles, holes and cavities on the tungsten sample surface were observed respectively. It is established that a noticeable erosion of tungsten and molybdenum samples as a result of irradiation with plasma flows simulating a stationary regime occurs only at relatively high sample surface temperatures.